(untitled) (Georgian Journal for European Studies, 2023)
Georgia, as the nation of the ‘associated trio’, recently was granted a clear ‘European perspective’, which transformed the country’s long-lasting pro-EU aspirations into a tangible result of extension of European Enlargement Policy towards the Eastern Partnership region. The unprovoked invasion and aggressive war launched by Russia in Ukraine triggered a need across the Western countries for a ‘paradigm shift’ in global approaches, which created for Tbilisi a unique chance to take the steps towards EU membership. At the same time the pressure has increased to keep the pace for the speedy democratic transformation and for the establishment of the rules based order, where the trust of the public in democratic institutions is increased. EU actorness had always been strong in Georgia, however, these developments broadened further its scope and presence in the country.